A Decolonial Critique of the South African Leave System in the Context of Traditional and Spiritual Responsibilities - Maanda, Muvhumbi Hasandi (University of the Witwatersrand, Johannesburg, 2023)
South Africa as a country consists of many cultures, traditions, religions and races. Hence it is often referred to as the rainbow nation, however the diversity of South Africa is often not reflected in its laws as such laws are of colonial origin. This research paper seeks to demonstrate that the current South African leave system as regulated by the Basic Conditions of Employment Act is of colonial origin and does not have regard to the cultural and religion landscape of South Africa. This will be done by looking at how the aforementioned legislation is colonial or western in nature to the detriment of the indigenous people of South Africa and other previously excluded races at the peak of colonisation. This paper will look at such traditional and spiritual responsibilities such as ancestral calling which are prevalent in South Africa’s employment relationship but remain unrecognised by the current leave system. This paper argues for the decolonisation of South Africa’s leave system in order to account for traditional and spiritual responsibilities.
A research report submitted in fulfillment of the requirements for the Master of Laws, in the Faculty of Commerce Law and Management, School of law, University of the Witwatersrand, Johannesburg, 2023
Keywords: UCTD; Ancestral calling; Kievits Kroon; Sangoma; Mmoledi; Sick leave; Family responsibility leave; decolonisation; SDG-10: Reduced inequalities